An analysis of relationship between Malaysia economic growth and foreign direct investment : review to Malaysian policies / Hapiza Omar, Hanani Ahmad Fuad and Nor Hidayah Harun - Omar, Hapiza; Ahmad Fuad, Hanani; Harun, Nor Hidayah (2012)
Sustained Economic Growth is a quantitative indicator to determine Malaysia’s performance. In this study economic growth is presented by Gross Domestic Product (GDP). There are many factors that influence economic growth and one of the factors is Foreign Direct Investment (FDI) that is discussed in this study. Past researchers have found that relationship between FDI and GDP is positive in the long run based on the country they studied by using different methodologies such as ordinary least square (OLS) regressions and Artificial Neutral Network (ANN). This study shows that FDI has relationship in the long run and no relationship in the short run. Based on the finding FDI and economic growth have unidirectional causality relationship and GDP causes FDI. Unit root, cointegration and granger causality test are conducted by using annual data of FDI and economic growth in Malaysia during the year 1970 to 2011 that are taken from the World Bank and the Ministry of Finance. This studied can be continued by looking at the specific factors of FDI, inward and outward. For the future study, future researcher can add the number of year 10 to 20 years, also can include other independence variables such as import and export, balance of payment or others that can influence economic growth.